Keeping quality of Red Chittagong Cows’ milk obtained under different hygienic conditions (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
To determine the effect of milking hygiene on keeping quality of milk at room temperature, 15 “Red Chittagong” milking cows were randomly and equally distributed under three different milking hygiene conditions (just previous to milking) such as T1=Washing and disinfection of udder and teats, milkers’ hands, and a sanitary rinse of milking pails with home-made calcium hypochlorite solution (200ppm Cl); T2=Washing of udder and teats, milkers’ hands, and milking pails with normal farm water; and T3=dry milking without any preparation of cows’ udder and teats , milkers’ hands and milking pails. Microbial study revealed an average Standard Plate Count (million cfu/ml) respectively for T1, T2, and T3 of 0.057±0.014, 0.708±0.8 and 0.161±0.037 at 0 hr; 0.263±0.080, 2.548±0.780 and 0.746±0.170 at 4 hr; 1.820±0.370, 18.711±5.050 and 5.578±1.840 at 8 hr; and 20.478±4.050, 25.578 ±2.200 and 22.367±3.400 at COB+ve. Average coliform count (thousand cfu/ml) were 0.038±0.024, 0.359±0.092 and 0.123±0.022 at 0 hr; 0.166 ± 0.100, 1.754±0.450 and 0.510±0.110 at 4 hr; 0.990±0.500, 12.810±4.010 and 3.350±0.850 at 8 hr; and 20.456±8.610, 25±5.440 and 24.440±5.460 at COB+ve respectively for T1, T2, and T3. Microbial counts up to 8hr were significantly (p